2019
DOI: 10.1111/myc.12987
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of A fumigatus‐specific IgG and galactomannan testing in the diagnosis of simple aspergilloma

Abstract: Summary Background An early diagnosis of chronic pulmonary aspergillosis (CPA) at the stage of simple aspergilloma (SA) remains a challenge in low‐ and middle‐income countries, where imaging may not be routinely available.ObjectiveWe investigate the role of Aspergillus fumigatus‐specific IgG in serum, and galactomannan (GM) in bronchoalveolar lavage fluid (BALF) and serum for the diagnosis of SA.MethodsWe included 46 consecutive treatment‐naïve subjects with SA. The 81 controls were subjects of treated pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 28 publications
1
31
0
2
Order By: Relevance
“…For commercial tests, there is also no standard cut-off values. The CPA category could justify different values and the possibility of other etiologies causing fungus ball [35]. Other possibilities for different cut-off values observed in our study may be related to the use of healthy or disease controls and ethnic differences.…”
Section: Discussionmentioning
confidence: 81%
“…For commercial tests, there is also no standard cut-off values. The CPA category could justify different values and the possibility of other etiologies causing fungus ball [35]. Other possibilities for different cut-off values observed in our study may be related to the use of healthy or disease controls and ethnic differences.…”
Section: Discussionmentioning
confidence: 81%
“…In present study, A. fumigatus-specific IgG positivity was defined as A. fumigatus IgG above 27 mgA/L (milligrams of antigen-specific antibodies per liter) [19e21]. While 50, 40 and 20 mgA/L have also been proposed, this cut-off was made because it has been used in the majority of publications [8,9,21,22]. The definition of rural or urban residency followed a previous local Taiwan study [23].…”
Section: Definition and Data Collectionmentioning
confidence: 99%
“…It has been estimated that patients with residual pulmonary cavities of ≥2 cm after TB treatment have a 20% chance of developing aspergillomas [8]. Recent studies conducted in high TB burden settings such as India and Uganda evaluating CPA in post-TB patients estimated CPA to be more common in cavitary disease [9,10]. Another study from Cuba also showed an association between high levels of Aspergillus immunoglobulin G (IgG) and the presence of cavities [11].…”
Section: Introductionmentioning
confidence: 99%